EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH PENERAPAN INISIASI MENYUSUI DINI TERHADAP SUHU TUBUH BAYI BARU LAHIR (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background : Early Breastfeeding Initiation (IMD) is a direct intervention that has the potential to significantly improve newborn outcomes, including reducing the risk of neonatal death, strengthening bonds of affection, extending the duration of breastfeeding, stabilizing the baby's body temperature, breathing, pulse, and blood glucose levels. IMD is done immediately after the baby is born for 1 hour. Purpose : To find out whether early initiation of breastfeeding has an effect on the body temperature of newborns. Methods : research conducted through literature search in several articles. Those Are Google Scoolar and Garuda. Results : There was an increase in axillary temperature of 0.4ºC ±0.3º in the IMD group while in the Non-IMD group, the temperature increased by 0.03º ±0.3ºC after one hour of birth. This study also shows that there is an effect between early initiation of breastfeeding and changes in the body temperature of newborns. Conclusions : The effect of IMD on the Newborn’s body temperature